The Whizz Pop Chocolate Shop - Saunders, Kate, 1960- (Delacorte Press, 2013)
Eleven-year-old twins Oz and Lily are recruited by a talking cat to assist her and M16 in foiling the dastardly plans of their great-great-uncle, a chocolatier who used magic to make a candy that bestows immortality.